Perancangan UI/UX Aplikasi Mobile Penjualan Kue dan Roti Menggunakan Metode Design Thinking (Studi Kasus: UMKM Ghonim Kue) - Nayaka Fajrina Soraya Rangkuti; Heni Wulandari; Randi Rian Putra (Jurnal Nasional Teknologi Komputer, 2025)
MSMEs are the backbone of the national economy, but many have yet to adapt to digital technology. MSMEs “Ghonim Kue” face challenges in reaching a wide range of customers because they still rely on conventional sales systems. This research aims to design the user interface (UI) and user experience (UX) of Ghonim Kue mobile application using the Design Thinking method. With several processes in it, among others, empathize, define, ideate, prototype, and testing are processes in implementing the design thinking method. The creation of this application uses Figma software as a mobile display designer and is tested using the System Usability Scale (SUS). The test results of 26 users showed a SUS score of 66.15 which is included in the “Adjective scale Good and Accepbility Marginal High” category. This design is expected to be a digital solution that can increase the competitiveness of Ghonim Kue MSMEs in the era of digital transformation.